2015
DOI: 10.1007/s00248-015-0599-2
|View full text |Cite
|
Sign up to set email alerts
|

Picophytoplankton as Tracers of Environmental Forcing in a Tropical Monsoonal Bay

Abstract: In order to better understand the picophytoplankton (PP) dynamics in tropical monsoon influenced coastal regions, samples were collected daily (June-September 2008: monsoon, December 2008: post-monsoon and April 2009: pre-monsoon) from a fixed station in Dona Paula Bay, India. Eight PP abundance peaks comprising Prochlorococcus-like cells, picoeukaryotes, and three groups of Synechococcus occurred. The chlorophyll biomass and PP abundance were negatively influenced by reduced solar radiation, salinity and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Moreover, a laboratory-grown culture experiment has shown that diatoms were not an exception to the rule that cell size reduces with increase in temperature (Montagnes and Franklin, 2001), where size-selective grazing may become a limiting factor for phytoplankton (Peter and Sommer, 2013). Pelagophyceae showed similar distribution patterns and most of the genera recovered in this study have been reported being dominant in warm surface water (Agawin et al, 2000; Mitbavkar et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, a laboratory-grown culture experiment has shown that diatoms were not an exception to the rule that cell size reduces with increase in temperature (Montagnes and Franklin, 2001), where size-selective grazing may become a limiting factor for phytoplankton (Peter and Sommer, 2013). Pelagophyceae showed similar distribution patterns and most of the genera recovered in this study have been reported being dominant in warm surface water (Agawin et al, 2000; Mitbavkar et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Picophytoplankton is composed of multiple populations spanning diverse physiological adaptations and ranges ( Rajaneesh et al, 2015 ; Tamm et al, 2018 ). Recent studies, in other estuarine and coastal areas, have separated Synechococcus / Cyanobium into pigment-based populations (PE-rich and PC-rich), suggesting differences in distribution patterns between the groups ( Mitbavkar et al, 2015 ; Li et al, 2019 ; Paerl et al, 2020 ). In this study, the three populations, PE-rich, PC-rich, and PPE, had significant differences in regard to (1) seasonal dynamics, (2) biomass contribution, (3) temperature regimes, and (4) nutrient limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in irradiance from summer to autumn can cause a transition from PE-rich to PC-rich ( Stomp et al, 2007 ). However, other environmental factors such as nutrient concentration may also influence the picocyanobacterial community composition ( Mitbavkar et al, 2015 ). PPE increase in abundance is thought to be related to low temperatures and high nutrient concentration ( Kuosa, 1991 ; Otero-Ferrer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Picophytoplankton is composed of multiple functional groups spanning diverse physiological adaptations and niches 17,29 . Recent studies, in other estuarine and coastal areas, have separated Synechococcus into pigment based functional groups (PE-rich and PC-rich) suggesting signi cant differences in distribution patterns between the groups 13,54,55 . In this study, the three functional groups, PE-rich, PC-rich and PPE and had signi cant differences in regard to, 1) seasonal dynamics, 2) biomass contribution, 3) temperature regimes, and 4) nutrient limitation.…”
Section: Discussionmentioning
confidence: 99%